Six-month humoral immune response to inactivated COVID-19 vaccine among people living with HIV - Zou, Shi; Guo, Wei; Wu, Songjie; Ming, Fangzhao; Tan, Yuting; Wu, Mengmeng; Tang, Weiming; Liang, Ke (Frontiers in Immunology, 2022)
Longitudinal humoral response to inactivated COVID-19 vaccines among people living with HIV (PLWH) have not yet been systematically investigated. We conducted a 6-month longitudinal study among vaccinated PLWH and HIV-Negative Controls (HNC) to determine whether the effects of the inactivated COVID-19 vaccine are different between the two groups of people. Totally, 46 PLWH and 38 HNC who received the inactivated COVID-19 vaccine on days 0 and 28 were enrolled. The SARS-CoV-2 neutralizing antibodies (nAbs) and total specific IgM and IgG antibodies were examined on Day 0-Day190. The level and positive seroconversion rate of nAbs peaked on Day 42 in HNC while peaked on Day 70 in PLWH, then decreased gradually with the extension of the vaccination period after the peaks. There was no significant difference in the peak positive seroconversion rate of nAbs between the two groups. However, the peak level of nAbs in PLWH (Day 70) was significantly lower than in HNC (Day 42, P =0.03). The decrease in the geometric mean concentrations (GMCs) of nAbs was observed as 42.9% in PLWH after peak level, which decreased from 8.07 BAU/mL [95% CI: 5.67-11.48] on Day 70 to 4.61 BAU/mL [95% CI: 3.35-6.34] on Day 190 (p = 0.02). On Day 190, only seven (18%, [95% CI: 6-40]) HNC and five (11%, [95% CI: 4-25]) PLWH maintained positive nAbs response respectively. The geometric mean ELISA units (GMEUs) and positive seroconversion rate of IgG in PLWH dropped significantly from Day 70 (GMEUs, 0.20 EU/mL, [95% CI: 0.13-0.34]; seroconversion, 52%, [95% CI: 34-69]) to Day 190 (GMEUs, 0.05 EU/mL, [95% CI: 0.03-0.08], P<0.001; seroconversion, 18%, [95% CI: 8-33], P<0.001). There was no significant difference in levels and seroconversion rates of nAbs and IgG between the two groups on Day 190.Both groups showed efficient humoral response to the inactivated COVID-19 vaccine. Although there was no significant difference in six-month immunogenicity between the two groups, the peak immunogenicity of the inactivated COVID-19 vaccine was delayed and lower in PLWH compared to HNC.